Digital Transformation of Land Transaction Income Tax Reporting through the Coretax System - Ni Made Dwi Wulandari; Johannes Ibrahim Kosasih; I Made Aditya Mantara Putra (Jurnal Smart Hukum (JSH), 2027)
The digital transformation of tax administration through the Coretax System has altered the mechanisms for fulfilling and verifying Income Tax obligations arising from the transfer of land and/or building rights. Although this transformation has strengthened service integration, it has also created functional tension because digital tax validation is a prerequisite for signing a deed, whereas the authentication of deeds by public officials requires certainty regarding the sequence, timing, and presence of the parties. This study analyzes the regulatory framework and legal implications of migrating Income Tax reporting to the Coretax System and reconstructs its implementing norms to ensure legal certainty in the event of system failure. This normative legal study employs statutory and conceptual approaches, supported by a limited sociological approach to contextualize the analysis, and applies qualitative-prescriptive analysis. The findings indicate that procedural misalignment, the absence of a uniform emergency mechanism, and the unclear allocation of responsibility for system disruptions may delay transactions and increase legal risks for taxpayers and Land Deed Officials (PPATs). The study proposes a three-stage model comprising pre-signing compliance, the signing session, and post-signing reconciliation, supported by a digital force majeure clause, an audit trail, and an official escrow account as emergency instruments. By placing tax compliance before the authentication session, the model ensures that digital efficiency does not undermine the authenticity of deeds or the legal protection of the parties